LOCAL FEATURES AND CHARACTERISTICS IN ARCHITECTURE OF TRADITIONAL INDIVIDUAL DWELLING OF THE STAVROPOL TERRITORY - Evgeny Leonidovich Budarin (Вестник Северо-Кавказского федерального университета)
The traditional rural dwelling reflects not only climatic features of the region, also it reflects specifics of existing cultural and community traditions, specific features of each family. The principle of flexible space-planning structure in the traditional rural individual dwelling always allows to adapt a house for changes of a functional purpose of rooms. The flexible space-planning decision gives an opportunity to change internal space of a house in the course of its exploitation.